Nurses’ adherence to ethical principles – A qualitative study - Wong, Valery (Nursing ethics, 2025)
BackgroundNursing is regulated by a set of professional standards. Whilst many forms of ethics apply to nursing, the biomedical ethical framework is common, involving autonomy, beneficence, non-maleficence and justice. In healthcare, nurses often encounter ethical dilemmas that require them to navigate conflicting ethical principles. However, how nurses adhere to these principles in such situations is unclear.Research AimTo explore how registered nurses adhere to ethical principles when dealing with ethical dilemmas at work.Research DesignA qualitative descriptive study design.Participants and Research ContextBetween August and December 2023, 21 registered nurses were recruited from a teaching hospital through purposive sampling. Data were collected through semi-structured in-person interviews or online video conferencing. Braun and Clarke’s thematic analysis approach was employed to analyse the data.Ethical ConsiderationsInterview participation was voluntary. Written consent was obtained before participation. Participants’ real identities were replaced with pseudonyms. This study was approved by the SingHealth Centralised Institutional Review Board.FindingsThe data analysis developed four major themes and 15 subthemes. The four major themes are “Addressing the dilemma,” “Contemplating the principles and consequences,” “Coordinating for well-informed, ethical decision,” and “Self-reflecting and finding consolation.”ConclusionThis study explains how nurses navigate and uphold ethical principles when caring for patients to the best of their ability. Fully adhering to ethical principles can be challenging for caring for actively dying patients. Further research can expound on nurses’ experiences and adherence to ethical principles in complex clinical cases.